2014
DOI: 10.4049/jimmunol.1301365
|View full text |Cite
|
Sign up to set email alerts
|

Gr-1dimCD11b+ Immature Myeloid-Derived Suppressor Cells but Not Neutrophils Are Markers of Lethal Tuberculosis Infection in Mice

Abstract: Tuberculosis disease (TB) may progress at different rates and have different outcomes. Neutrophils have been implicated in TB progression; however, data on their role during TB are controversial. Here we show that in mice, TB progression is associated with the accumulation of cells that express neutrophilic markers Gr-1 and Ly-6G, but do not belong to conventional neutrophils. The cells exhibit unsegmented nuclei, have Gr-1dimLy-6GdimCD11b+ phenotype and express F4/80, CD49d, Ly-6C, CD117, CD135 markers charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 45 publications
6
115
0
2
Order By: Relevance
“…Interestingly, the authors also reported that the frequency of MDSC returned to the levels and maturation status of healthy individuals after successful antibiotic treatment and concluded that MDSC induced after exposure to M. tuberculosis may contribute to the inability of the host to eliminate the bacterium and thus to disease development [16]. Association of MDSC expansion with tuberculosis progression has also been observed in murine models of M. tuberculosis infection [17,18]. Specifically, Tsiganov et al [17] reported that tuberculosis progression in mice that developed severe disease was associated with the replacement of Gr-1 high Ly6G high conventional neutrophils by a population of Gr-1 dim CD11b + cells that suppressed T-cell proliferation and IFN-gamma production in vitro via NO-dependent mechanisms and that resembled MDSC.…”
Section: Mdsc In Bacterial Infectionsmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the authors also reported that the frequency of MDSC returned to the levels and maturation status of healthy individuals after successful antibiotic treatment and concluded that MDSC induced after exposure to M. tuberculosis may contribute to the inability of the host to eliminate the bacterium and thus to disease development [16]. Association of MDSC expansion with tuberculosis progression has also been observed in murine models of M. tuberculosis infection [17,18]. Specifically, Tsiganov et al [17] reported that tuberculosis progression in mice that developed severe disease was associated with the replacement of Gr-1 high Ly6G high conventional neutrophils by a population of Gr-1 dim CD11b + cells that suppressed T-cell proliferation and IFN-gamma production in vitro via NO-dependent mechanisms and that resembled MDSC.…”
Section: Mdsc In Bacterial Infectionsmentioning
confidence: 91%
“…Association of MDSC expansion with tuberculosis progression has also been observed in murine models of M. tuberculosis infection [17,18]. Specifically, Tsiganov et al [17] reported that tuberculosis progression in mice that developed severe disease was associated with the replacement of Gr-1 high Ly6G high conventional neutrophils by a population of Gr-1 dim CD11b + cells that suppressed T-cell proliferation and IFN-gamma production in vitro via NO-dependent mechanisms and that resembled MDSC. The study of Knaul et al [18] confirmed that excessive accumulation of MDSC in the lungs of M. tuberculosis-infected mice enhanced disease lethality and indicated that MDSC provided a niche for M. tuberculosis survival within the infected lungs.…”
Section: Mdsc In Bacterial Infectionsmentioning
confidence: 94%
“…It is possible, however, that during these late stages of lethal Mtb infection, the Ly6G and Gr-1 expressing population might not reflect true neutrophils Lyadova et al 2010). Moreover, these cells share characteristics of immature myeloidderived suppressor cells, and future studies have to determine their role in tuberculosis pathogenesis (Obregó n- Henao et al 2013;Tsiganov et al 2014). …”
Section: Neutrophilsmentioning
confidence: 99%
“…In a mouse model of TB, Tsiganov et al (2014) showed that at the pre-lethal stage, MDSCs accumulate in the lungs, bone marrow, spleen and blood. These findings suggest that MDSCs play a role in TB pathogenesis and the increased numbers of these cells in old age may contribute to the reduced immunity to TB in some older adults.…”
Section: Infections Mdscs and Ageingmentioning
confidence: 99%